Autoavaliação institucional e suas articulações com a reformulação curricular de cursos de graduação - Martins, Clícia Bührer (2016)
This doctoral thesis presents the analysis of the institutional self-assessment process of the undergraduate courses at the Ponta Grossa State University – PR, and its articulations with the curricular reform of the pedagogical projects of undergraduate courses from the same institution. The following research question guided the investigation: Does the institutional self-assessment process contributes to the curricular reform of the pedagogical projects of undergraduate courses at the UEPG? The aims of the study were: a)identify the elements that emerged from self-assessment of the undergraduate courses for the process of curricular reform; b) check if the results from this self-assessment are the object of reflection, problematization and actions in the process of curricular reform and c) establish the relations between the self-assessment of the undergraduate courses and the curricular reform processes. The research was carried out at the UEPG and involved 8 undergraduate courses, and the research participants were course coordinators and institutional managers. The research was carried out according to a qualitative approach, which used content analysis in addition to interviews and documental analysis. The interviews were analyzed and produced 7 empirical categories: the curriculum assessed, participation, collective process of self-assessment of courses and curricular reform, mobilization of those involved: teachers and students, the role of course coordinators, use of the results from self-assessment of the undergraduate courses, potentialities and weaknesses of undergraduate self-assessment. The theoretical-methodological framework included authors such as Dias Sobrinho (2000), (2003), (2008), (2010), Afonso (2009), Leite (2009), Saul (2010), Cappelletti (2012), (2010), Chizzotti (1991), (2009), Bardin (1977), Estrela and Rodrigues (1995), Polidori (2009), (2011), Lima (1997), (2015). The results of the research point out that institutional self-assessment of the undergraduate course contributes to the curricular reform of the pedagogical projects at the UEPG, especially in terms of discussions and collective reflections about courses’ needs, strong and weak points concerning the disciplines within the courses, contents, relation between theory and practice, teaching process, number of teaching hours and issues related to students´ professional education. The self-assessment process was not characterized by linearity, but by a set of actions marked by ups and downs, advances and setbacks, conflicts and contradictions that to an extent typical characteristics of an evaluation process done according to a participatory perspective that involves the members responsible for it